New particle formation events in semi-clean South African savannah - V. Vakkari (Atmospheric Chemistry and Physics, 2011)
This study is based on 18 months (20 July 2006–5 February 2008) of continuous measurements of aerosol particle size distributions, air ion size distributions, trace gas concentrations and basic meteorology in a semi-clean savannah environment in Republic of South Africa. New particle formation and growth was observed on 69% of the days and bursts of non-growing ions/sub-10 nm particles on additional 14% of the days. This new particle formation frequency is the highest reported from boundary layer so far. Also the new particle formation and growth rates were among the highest reported in the literature for continental boundary layer locations; median 10 nm formation rate was 2.2 cm−3 s−1 and median 10–30 nm growth rate 8.9 nm h−1. The median 2 nm ion formation rate was 0.5 cm−3 s−1 and the median ion growth rates were 6.2, 8.0 and 8.1 nm h−1 for size ranges 1.5–3 nm, 3–7 nm and 7–20 nm, respectively. The growth rates had a clear seasonal dependency with minimum during winter and maxima in spring and late summer. The relative contribution of estimated sulphuric acid to the growth rate was decreasing with increasing particle size and could explain more than 20% of the observed growth rate only for the 1.5–3 nm size range. Also the air mass history analysis indicated the highest formation and growth rates to be associated with the area of highest VOC (Volatile Organic Compounds) emissions following from biological activity rather than the highest estimated sulphuric acid concentrations. The frequency of new particle formation, however, increased nearly monotonously with the estimated sulphuric acid reaching 100% at H2SO4 concentration of 6 · 107 cm−3, which suggests the formation and growth to be independent of each other.